1997
DOI: 10.1128/jvi.71.9.6956-6966.1997
|View full text |Cite
|
Sign up to set email alerts
|

Cell-type-specific separate regulation of the E6 and E7 promoters of human papillomavirus type 6a by the viral transcription factor E2

Abstract: Gene expression of human papillomaviruses (HPV) is tightly controlled by cellular factors and by the virally encoded E2 protein through binding to distinct sites within the regulatory noncoding region. While for the high-risk genital papillomaviruses a single promoter drives the expression of all early genes, a second promoter present in the E6 open reading frame of the low-risk HPV type 6 (HPV6) would allow an independent regulation of E6 and E7 oncogene expression. In this report, we provide the first eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 55 publications
0
24
0
2
Order By: Relevance
“…With consequently rising concentrations, E2 also binds to the lowaffinity proximal E2BS3 and E2BS4. This represses transcription from the p97 promoter and thereby maintains the levels of E6 and E7 at a low and autoregulated level as shown in Figure 1A 9,10,12 and as reviewed by von Knebel Doeberitz and Vinokurova 11 (note that the numbering of E2BSs in the study by von Knebel Doeberitz and Vinokurova 11 differs from that currently used).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…With consequently rising concentrations, E2 also binds to the lowaffinity proximal E2BS3 and E2BS4. This represses transcription from the p97 promoter and thereby maintains the levels of E6 and E7 at a low and autoregulated level as shown in Figure 1A 9,10,12 and as reviewed by von Knebel Doeberitz and Vinokurova 11 (note that the numbering of E2BSs in the study by von Knebel Doeberitz and Vinokurova 11 differs from that currently used).…”
Section: Introductionmentioning
confidence: 91%
“…7 The most important transcriptional regulator of E6 and E7 oncogene expression is the viral E2 protein, which binds to 4 E2-binding sites (E2BSs1, 2, 3, and 4) in the URR. 8 The current model of E2 function in the host cells during the normal viral life cycle implies that E2 binds with high affinity to the E2BS1, resulting in activation of the p97 early promoter even at low E2 concentrations, 9,10 as reviewed by von Knebel Doeberitz and Vinokurova. 11 This promoter activation results in enhanced expression of the early viral proteins, including the oncoproteins E6 and E7 and E2 itself.…”
Section: Introductionmentioning
confidence: 99%
“…If the concentration of the E2 protein rises beyond a certain level, E2 binds also to the low affinity proximal E2BSs (E2BS2, 3 and 4) and represses transcription from the early promoter p97 through displacement of Sp1 and TBP from their respective binding sites, thereby keeping the levels of E6 and E7 under control. [11][12][13] Accordingly, it has been suggested that deregulated expression of E6 and E7 oncogenes and initiation of the transformation process may result from loss of the E2 repressive functions. Viral integration into the host genome usually occurs downstream of the E6 and E7 genes, often in E1 and E2 regions 14,15 and results in a loss of negative-feedback control of oncogene expression.…”
mentioning
confidence: 99%
“…The binding of E2 protein to the different E2 binding sites will exert either transcriptional activation or repression on the E6/E7 promoter, depending on their distance from the TATA box of the promoter [Dostatni et al, ]. Binding to E2BS4 (the E2 binding site distal to TATA box of E6/E7 promoter) results in transcriptional activation whereas binding to E2BS1 or E2BS2 (the E2 binding sites proximal to TATA box of E6/E7 promoter) results in transcriptional repression through displacement of Sp1 and TBP from their binding sites [Dong et al, ; Demeret et al, ; Rapp et al, ; Steger and Corbach, ; Soeda et al, ]. Hence, at low concentration of E2, it is expected that E2 protein will bind to E2BS4, exerting transcriptional activation on the E6/E7 promoter and when the E2 protein concentration increases, more E2 protein will bind to E2BS1&2 relative to E2BS4, resulting in transcriptional repression [Doeberitz and Vinokurova, ].…”
Section: Introductionmentioning
confidence: 99%